Evaluation of treatment patterns and survival among patients with diffuse large B-cell lymphoma in the USA. (13th February 2019) - Morrison, Vicki A; Shou, Yaping; Bell, Jill A; Hamilton, Laurie; Ogbonnaya, Augustina; Raju, Aditya; Hennenfent, Kristin; Eaddy, Michael; Galaznik, Aaron
Aim: To evaluate treatment patterns of diffuse large B-cell lymphoma (DLBCL).Patients & methods: First-line and relapsed/refractory treatment patterns and survival outcomes following first-line therapy in adult patients newly diagnosed with DLBCL were evaluated.Results: A total of 1436 DLBCL patients initiated treatment and mainly received a combination regimen versus monotherapy (92.1 vs 7.9%). Patients who received monotherapy were older with more comorbidities and had shorter progression-free survival than patients receiving combination therapy (median: 31.3 vs 55.8 months). In the second-line setting (n = 164), rituximab-based combination regimens were most common; 25% underwent stem cell transplantation, and were younger with fewer comorbidities.Conclusion: These results illustrate the need for new treatment options for patients unable to tolerate initial combination therapy and transplant-ineligible patients who require salvage therapy.